THE EFFECT OF GREEN RECRUITMENT, GREEN TRAINING ON ENVIRONMENTAL PERFORMANCE IN PT WIRA CIPTA PERKASA USING EMPLOYEE GREEN BEHAVIOR AS MEDIATION VARIABLE - Mayangsari, Resti Eva; Nawangsari, Lenny Christina (Dinasti International Journal of Management Science, 2019)
Environmental performance is an attempt to create the company's performance green environment. The purpose of this study to analyze the influence Effect of Green Recruitment, Training Green Environmental Performance Against the Green Employee Behavior As Variable Mediation. This type of research using quantitative research with survey method. This research was conducted at PT Wira Cipta Perkasa and use methods of sampling probability sampling and the sampling technique is simple random sampling. A total sample of 100 people, Data analysis techniques in this study using Structural Equation Modeling (SEM) using PLS (Partial Least Square) as a software, The results of this study prove Green Recruitment, Green Training and Employee Green Behavior positive and significant effect on the behavior of environmental performance.